Maximizing machinery uptime - Geitner, Fred K.; Bloch, Heinz P., 1933- (Amsterdam ; Boston : Elsevier Gulf Professional Pub., 2006)
The authors use their decades of experience and draw upon real-world examples to demonstrate that the application of their techniques provides a basis for equipment management, uptime maximization, and reduced maintenance costs. The text explores reliability assessment techniques such as Failure Mode, Effect Analysis, and Fault Tree Analysis of commonly encountered rotating machinery. These are all highly effective techniques that the engineer can apply to maximize uptime and thereby maximize production and profitability. *Provides the tools to drastically improve machinery productivity and performance *Bridges the gap between the theory of "reliability engineering" and the practical day-to-day measures that lead to machinery uptime *Authoritative reference for maximizing the uptime of process equipment.
Introduction -- The meaning of reliability -- Uptime as probability of success -- Estimating machinery uptime -- Is there a universal approach to predicting machinery uptime? -- Predicting uptime of turbomachinery -- Failure mode and effect analysis -- Fault tree analysis -- Machinery risk and hazard assessment -- Machinery system availability analysis -- Practical field uptime assessment -- Life-cycle cost analysis -- Starting with good specifications -- Owner contractor interfaces and equipment availability -- The operational environment -- The maintenance environment -- Continuous improvement -- Review of mechanical structures and piping for machinery.
Includes bibliographical references and index.
Keywords: Industrial management; Machinery in the workplace; Electronic books